2018
DOI: 10.1111/all.13406
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of allergic rhinitis using mobile technology with real‐world data: The MASK observational pilot study

Abstract: Background Large observational implementation studies are needed to triangulate the findings from randomized control trials as they reflect “real‐world” everyday practice. In a pilot study, we attempted to provide additional and complementary insights on the real‐life treatment of allergic rhinitis (AR) using mobile technology. Methods A mobile phone app (Allergy Diary, freely available in Google Play and Apple App stores) collects the data of daily visual analog scales (VAS) for (i) overall allergic symptoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
204
0
22

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(231 citation statements)
references
References 30 publications
5
204
0
22
Order By: Relevance
“…Lack of understanding of medication usage is common in all chronic diseases. Studies of patients using the MASK app show that users´ behavior is often not in accord with guidelines, but patients frequently treat themselves as needed, which results in only less than 5% taking medication according to guideline recommendations . These results prompted ARIA to develop a self‐management strategy rather than targeting an increase in adherence.…”
Section: Mhealth In Allergic Diseasesmentioning
confidence: 99%
“…Lack of understanding of medication usage is common in all chronic diseases. Studies of patients using the MASK app show that users´ behavior is often not in accord with guidelines, but patients frequently treat themselves as needed, which results in only less than 5% taking medication according to guideline recommendations . These results prompted ARIA to develop a self‐management strategy rather than targeting an increase in adherence.…”
Section: Mhealth In Allergic Diseasesmentioning
confidence: 99%
“…ICPs have been proposed with a focus on mHealth technologies that should enhance self‐management and adherence to guidelines and ICPs. An innovative patient‐centered approach for ICPs has been proposed by the ARIA expert group for rhinitis and asthma multi‐morbidity …”
Section: Next‐generation Care Pathways Of Cat Allergymentioning
confidence: 99%
“…Mobile applications have been developed to monitor the symptoms, medication usage, and quality of life of the disease more efficiently and in a timely manner, 73-75 becoming of relevant importance for patient stratification. 76 In this regard, a large, cross-sectional, mul- 75 Furthermore, the study demonstrated that MASK diary is useful in evaluating daily AR management in a large population regardless of geographic, cultural, and linguistic differences. 75…”
Section: Patient Educationmentioning
confidence: 87%